Dimensions of materialism and credit card usage: an application and extension of the theory of planned behavior in Bangladesh. Issue 3 (December 2018) - Ahamed, A.; Limbu, Yam
Abstract This empirical test of an extended model of the theory of planned behavior (TPB) applies three dimensions of materialism (success, centrality, and happiness) to predict consumers' attitudes and behavioral intentions toward credit card use in a developing, non-Western country. The data, from 373 Bangladeshi credit card users, confirm the applicability of the TPB for explaining the credit card attitudes and intentions among this consumer sample. Success is the most important materialism dimension, with significant positive relationships with attitudes and social norms. Happiness exhibits an unexpectedly positive and significant association with perceived behavioral control (PBC). Both attitude and PBC mediate the relationships of success and centrality with intentions, whereas social norms do not. In a double mediation effect of subjective norms, this relationship arises through attitude and PBC. These findings accordingly provide a more comprehensive view of materialism and the applicability of the TPB in a developing, non-Western country.